Assessment of the spread of diseases caused by medical and social problems (Environment & Health, 2025)
The purpose of the study was to analyze the epidemic situation with the spread of diseases caused by medical and social problems under martial law in Ukraine.Materials and methods: search, bibliosemantic historical, analytical and descriptive methods were used.Results: In the context of martial law in Ukraine, medical and social problems have become more acute. In order to ensure the conditions for preserving the mental health of the population and the mental health of healthcare professionals, the following was substantiated: creation of conditions at the level of outpatient clinics for the provision of psychological and psychotherapeutic assistance to the population; psychological support for all working healthcare professionals during their work shift (one psychologist for every 75 employees of the work shift), which is implemented in the regulatory framework of sanitary and urban planning legislation: Sanitary and Epidemiological Norms and Regulations No. 354-2023 and DBN B.2.2-10:2022 and meets the requirements of the Concept for the Development of Mental Health Care in Ukraine until 2030 and the European Social Charter.Conclusion: Against the backdrop of military operations unfolding in Ukraine, medical and social problems are worsening and the general health of society is deteriorating, which requires preventive actions.
Keywords: epidemic situation; diseases; medical and social problems; tuberculosis; mental disorders; tobacco use; martial law